Effect of Vitamin D Supplementation on Insulin, Fasting Blood Glucose, and Waist-Hip Ratio in Young Females with Pre-existing Vitamin D Deficiency - Mona Hmoud AlSheikh; Shayma Ibrahim Almubayadh (The Prodia Education and Research Institute (PERI), 2019)
BACKGROUND: Vitamin D is an essential nutrient requirement for adults and children for normal metabolism and maintenance of healthy bones. Its deficiency may disrupt homeostasis and contribute to systemic diseases, especially in obese patients. This study aimed to examine the effect of vitamin D on insulin, fasting blood glucose (FBG) and waist-hip ratio (WHR) in young and obese Saudi females with pre-existing hypovitaminosis D.METHODS: The results of this study were based on prospective parallel randomised controlled clinical trial conducted at King Fahd University Hospital in which 30 obese Saudi young females aging 18-23 years with preexisting vitamin D deficiency contributed. Participants were randomly assigned to either vitamin D supplementation group (experimental) or placebo group (control). Subjects of vitamin D group received 50,000 IU/week of cholecalciferol drops and placebo group received 10 mL of normal saline drops for 12 weeks.RESULTS: The results of multivariate repeated measures analysis showed a change in serum 25-Hydroxycholecalciferol levels after vitamin D supplementation (F=296.132, p<0.05). There was also an indication of difference between the vitamin D group and placebo group. The only significant relationship was found between vitamin D and FBG (p<0.05). Supplementation of vitamin D improved FBG but did not contribute to improving insulin level. There was no association between vitamin D supplementation and WHR.CONCLUSION: This study concludes that supplementation of vitamin D improves FBG, but it has no contribution in improving insulin level. No association exists between vitamin D supplementation and WHR. The insignificant correlation of vitamin D intake with WHR and insulin can be attributed to the small sample size, therefore, further research is suggested with large sample size.KEYWORDS: vitamin D, fasting blood glucose, body mass index, waist hip ratio, hypovitaminosis D